FROM MOBILIZATION TO POLITICIZATION: UNDERSTANDING POLITICAL DYNAMICS OF COMMUNITY-BASED URBAN FOOD SECURITY POLICY IN CITY OF MAKASSAR - Sudarmono, Sudarmono (Universitas Padjadjaran, 2024)
Since decentralization was reinforced in 1999, local politicians have exploited local policies to enhance their popularity and electability. In this study, I describe the implementation of a food security policy to demonstrate how the local arena had undergone massive political dynamics through unintegrated food governance demonstrated by local governments in Makassar City. This article aims to analyze the dynamic of urban food policy implemented by the municipality from 2013 to 2023. A qualitative approach had been employed through a case study of the implementation of food security policy. Data were collected by snowball method to eminent informants. Also, focus group discussions were employed in certain community groups. This study found that food policy in Makassar City during the study period had shown a political mobilization rather than a pure food security policy to help the community. In the policy planning, the failure was found in the limited technical analysis. The people who dwell in this city were not prepared for agricultural activities, including planting, maintaining the plants, and soil treatment. Also, the typical vegetables that were planted were not suitable for the climatic characteristics of this city. This study also found that media framing was massively exploited to escalate the positive framing of the ‘inclusivity’ of the leadership and attract the people to engage beyond food diversification. On the other side, as this policy was funded through a discretionary approach, massive negative sentiment had emerged, particularly from the legislative. They felt like an abandoned partner. Consequently, the government should create an alternative mechanism through shadow bureaucrats, designed by the mayor.